Structural behavior of prestressed pretensioned concrete composite section - Abdul Abbas, Zaid F. (2009)
Composite construction in prestressed concrete usually consists of precast, prestressed members acting in combination with a cast-in-situ concrete component. This study investigates the structural behavior of a JKR prestressed pretensioned precast concrete T-Beam (PRT) made composite by a cast-in-situ slab. The precast beam was scaled down by one half of the full-scale JKR PRT1 beam. The composite beam is constructed using the un-shored construction method and tested for flexural using two point loads. Load-deflection response, crack development, distribution of strain across the depth of the composite section, mode of failure and ultimate flexural strength capacity are measured and analyzed. The results show that the JKR Standard Beams (Pretensioned Concrete Composite T-Beam), and cast-in-situ slab has no significant difference in its structural behavior compared to the results from other research.